International disasters in Asia Pacific: Indonesia's civil-military responses - Sembiring, Margareth (2016)
Long a recipient of international assistance during ‘natural’ disasters, Indonesia has been recently stepping up its joint civil-military humanitarian responses in the Asia Pacific. What does this mean for Indonesia and the world disaster response?